Taboo for Taboo Strategy in Indonesian-English Translation of Taboo Words in Inang Movie Subtitles - Mukminin, Muhamad Saiful; Muhhit, Ahmad Abdul; Ahmed, Aqeel (Institut Agama Islam Negeri Parepare, 2025)
The present research aims to explore and describe the translation strategies of taboo words in the subtitles of the movie Inang, available on the Netflix platform. Using a descriptive qualitative approach, the study focuses on analyzing Indonesian taboo words translated into English, identifying the strategies applied, and investigating how subtitling can either preserve or alter their intensity and meaning in cross-linguistic and cross-cultural adaptation. The research data was gathered by watching Inang on Netflix, noting the use of taboo words in the Indonesian subtitles, along with their English translations. Data collection involved identifying 23 taboo words or phrases and recording their corresponding timestamps. The collected data was analyzed using interactive data analysis model, which includes data reduction, data presentation, and conclusion drawing. The analysis revealed two types of the taboo-for-taboo strategy: the first is the taboo for taboo strategy that maintains the same level of taboo as the source language, maintaining its intensity. While the second is the taboo for taboo strategy with a lower level of taboo compared to the source language. In conclusion, the study shows that the taboo-for-taboo strategy in Inang allows for a balanced adaptation of offensive expressions.